TEACHING ‘JACK’ PROVERBS TO UZBEK LEARNERS: MULTIFACETED CHALLENGES AND EFFECTIVE TEACHING STRATEGIES (Universal International Scientific Journal, 2026)
This study examines teaching ‘Jack’ proverbs to Uzbek learners: multifaceted challengesand effective teaching strategies. Content analysis of The Oxford Dictionary of Proverbs and selectedcourse books revealed difficulties in polysemy, figurative meaning, pragmatic interpretation, stylisticfeatures, and cross-linguistic interference. To address these, the study proposes various learner-centeredstrategies. A task-based learning sample illustrates practical classroom application, promotingcontextualized, learner-centered instruction. The study focuses on Jack proverbs due to their frequencyand relevance in course books, the tasks can be adapted to learners’ proficiency and interests. Furtherresearch may apply these instructional strategies to proverbs containing different anthroponyms to fosterdeeper figurative and cultural understanding
Keywords: anthroponyms; English Jack proverbs; figurative